Relationship between Psychological Capital and Sleep Quality in Intensive Care Unit Nurses - Sahar Sajedi; Ezzat Jafarjalal; Shima Haghani (Iran University of Medical Sciences, 2022)
Background: Adequate sleep is essential for proper physical and mental functioning. This study aims to investigate the relationship between the psychological capital and sleep quality of nurses working in Intensive Care Units (ICUs).  Methods: This is a descriptive correlational study conducted in 2021. Participants were 200 ICU nurses selected from hospitals affiliated to Iran University of Medical Sciences using a proportionate stratified sampling method. Data were collected by McGee's Psychological Capital Questionnaire (PCQ) and the Pittsburgh Sleep Quality Index (PSQI) and were analyzed using Pearson correlation test in SPSS v.16. The significance level was set at 0.05. Results: There was a significant negative relationship between PCQ subscales and the components of PSQI (P<0.05). The nurses' psychological capital had a significant negative relationship with their working hours (P<0.001), work experience (P=0.04) and work experience in ICUs (P=0.03). Moreover, their sleep quality had a significant relationship with their shiftwork status (P<0.001) and work experience (P=0.04). Conclusion: Improved sleep quality is associated with increased psychological capital and its components in ICU nurses. Therefore, it is necessary for these nurses to have adequate and quality sleep for proper performance and success at workplace.